Pengaruh Kualitas Produk, Harga dan Promosi Terhadap Perpindahan Merek Sabun Mandi Lifebuoy pada Ibu Rumah Tangga di Desa Purwokerto Lor Kabupaten Banyumas - arinastuti arin; Dian Safitri (FEB UNWIKU PURWOKERTO, 2021)
This study aims to analyze the effect of product quality, price and promotion to brand switching on Lifebuoy bath soap among housewives in Purwokerto Lor Village, Banyumas Regency. This type of research is quantitative with multiple linear regression research methods. The results showed that product quality, price and promotion had a positive and significant effect to brand switching on Lifebuoy bath soap in Purwokerto Lor Village, Banyumas Regency. The policy implication of this finding is that companies should further improve product quality, price and promotion, because the motive for housewives switching Lifebuoy soap is to seek variety.